Pengaruh Profitabilitas, Leverage, Sales Growth, dan Komite Audit terhadap Tax Avoidance pada Perusahaan Manufaktur Sektor Industri yang terdaftar di Bursa Efek Indonesia tahun 2017-2021 - Herlina Sari, Maydiani Putri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The practice of tax avoidance in Indonesia is rife, both in small and large companies. This is indicated by the decline in the performance of the Indonesian government in achieving the target of state revenue sourced from the tax sector. Based on this thought, researchers see an urgency to conduct research that discusses the driving aspects of tax avoidance, especially in Indonesia. The research method used in this study is a quantitative method. This study analyzes business entities in the manufacturing group, namely 39 companies that have been listed on the IDX (Indonesian Stock Exchange), which are limited in scope to the industrial sector with a research period of 5 years (2017–2021). The 39 sample companies were selected through a purposive sampling technique. The process of analyzing the data utilizes multiple linear regression methods. Aspects that become test variables are tax avoidance, profitability, sales growth, leverage, and the audit committee. The results of this study prove that tax avoidance is affected by profitability, sales growth, and leverage. However, the audit committee showed no effect on tax evasion.